2009
DOI: 10.1111/j.1365-2826.2009.01927.x
|View full text |Cite
|
Sign up to set email alerts
|

Oestradiol and Insulin‐Like Growth Factor‐1 Reduce Cell Loss after Global Ischaemia in Middle‐Aged Female Rats

Abstract: Whereas the ability of oestradiol and insulin-like growth factor-1 (IGF1) to afford neuroprotection against ischemia-induced neuronal death in young female and male rodents is well established, the impact of IGF1 in middle-aged animals is largely unknown. This study assessed the efficacy of oestradiol and IGF1 in reducing neuronal death after transient global ischemia in middle-aged female rats following an 8-week hormone withdrawal. Rats were ovariohysterectomized (OVX) and implanted 8 weeks later with an osm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
28
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 24 publications
(29 citation statements)
references
References 54 publications
(64 reference statements)
1
28
0
Order By: Relevance
“…Middle-aged rats underwent pellet implantation (0.1 mg, 60d sustained release; Innovative Research of America) or sham surgery 8 weeks after OVX. In recent reports (De Butte-Smith et al, 2009; Traub et al, 2009) we found that estradiol was effective in rescuing CA1 pyramidal neurons from ischemia-induced cell death in middle-aged rats that were OVX for 8 weeks before experimentation. Hence, we used the 8 week OVX duration as these animals would be similar to women who are 5–10 years post-menopause.…”
Section: Methodsmentioning
confidence: 84%
See 4 more Smart Citations
“…Middle-aged rats underwent pellet implantation (0.1 mg, 60d sustained release; Innovative Research of America) or sham surgery 8 weeks after OVX. In recent reports (De Butte-Smith et al, 2009; Traub et al, 2009) we found that estradiol was effective in rescuing CA1 pyramidal neurons from ischemia-induced cell death in middle-aged rats that were OVX for 8 weeks before experimentation. Hence, we used the 8 week OVX duration as these animals would be similar to women who are 5–10 years post-menopause.…”
Section: Methodsmentioning
confidence: 84%
“…In contrast, we recently demonstrated that estradiol pretreatment is neuroprotective in middle-aged females that are OVX for 8 weeks prior to insult (De Butte-Smith et al, 2009; Traub et al, 2009). Hence, the current study investigated the effects of estradiol on the phosphorylation status of several key molecular targets involved in neuronal survival, such as Akt, CREB, and STAT3, in middle-aged female rats subjected to global ischemia 8 weeks after OVX.…”
Section: Discussionmentioning
confidence: 91%
See 3 more Smart Citations